2021
DOI: 10.1016/j.devcel.2021.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Mauve/LYST limits fusion of lysosome-related organelles and promotes centrosomal recruitment of microtubule nucleating proteins

Abstract: Summary Lysosome-related organelles (LROs) are endosomal compartments carrying tissue-specific proteins, which become enlarged in Chediak-Higashi syndrome (CHS) due to mutations in LYST . Here, we show that Drosophila Mauve, a counterpart of LYST , suppresses vesicle fusion events with lipid droplets (LDs) during the formation of yolk granules (YGs), the LROs of the syncytial embryo, and opposes Rab5, which promotes fusion. Mauve l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 66 publications
(73 reference statements)
1
17
0
Order By: Relevance
“…5a arrow), as well as the YV size heterogeneity and autofluorescence variability reported for stronger allele combinations (Fig. 5a) 23 , but no obvious association between GGs and LDs (Fig. 5b) 23 .…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…5a arrow), as well as the YV size heterogeneity and autofluorescence variability reported for stronger allele combinations (Fig. 5a) 23 , but no obvious association between GGs and LDs (Fig. 5b) 23 .…”
Section: Resultsmentioning
confidence: 68%
“…Mauve is a resident protein on lysosome related organelles (LROs) important for their maturation. YVs are a type of LRO and in the absence of Mauve display several phenotypes, including an association with LDs 23 . Might these YV-LD interactions affect nutrient sorting?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding cytotoxicity, although one study reported that the smaller size of the cortical actin mesh at the CS relative to the enlarged LGs prevented degranulation in CHS1/LYST -deficient NK cells ( 93 ), important roles of CHS1/LYST in LG polarization to the CS have also been suggested ( 91 ). In addition, Mauve, the Drosophila homolog of CHS1/LYST, not only regulates vesicle fusion of yolk granules (the secretory lysosomes of the Drosophila embryo) but was also found to regulate microtubule nucleation from the microtubule organizing center (MTOC) ( 94 ). Therefore, future studies are required to better elucidate the molecular details by which CHS1/LYST regulates the lysosomal fusion/fission process and the impact on cytotoxic activity.…”
Section: Biogenesis Of Lytic Granulesmentioning
confidence: 99%
“…Additional theories of nucleating MTs at the cortex were recently proposed in the context of lipid droplets (LD) and yolk granules (YG) and the possibility that LD-associated proteins can exert control on MT nucleation from centrosomes [ 24 ]. One of these proteins associated with YGs was shown to be Mauve/LYST.…”
Section: Introductionmentioning
confidence: 99%